2021
DOI: 10.4153/s0008414x21000420
|View full text |Cite
|
Sign up to set email alerts
|

Unique continuation properties for polyharmonic maps between Riemannian manifolds

Abstract: Polyharmonic maps of order k (briefly, k-harmonic maps) are a natural generalization of harmonic and biharmonic maps. These maps are defined as the critical points of suitable higher order functionals which extend the classical energy functional for maps between Riemannian manifolds. The main aim of this paper is to investigate the so-called unique continuation principle. More precisely, assuming that the domain is connected, we shall prove the following extensions of results known in the harmonic and biharmon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…For the current status of research on polyharmonic maps we refer to [2], polyharmonic hypersurfaces in Riemannian space forms have been investigated in [17], this analysis has recently been extended to the pseudo-Riemannian case in [3]. Unique continuation properties for polyharmonic maps were obtained in [7], a structure theorem for polyharmonic maps from complete non-compact Riemannian manifolds was established in [6].…”
Section: Introduction and Resultsmentioning
confidence: 99%
“…For the current status of research on polyharmonic maps we refer to [2], polyharmonic hypersurfaces in Riemannian space forms have been investigated in [17], this analysis has recently been extended to the pseudo-Riemannian case in [3]. Unique continuation properties for polyharmonic maps were obtained in [7], a structure theorem for polyharmonic maps from complete non-compact Riemannian manifolds was established in [6].…”
Section: Introduction and Resultsmentioning
confidence: 99%
“…Hypersurfaces in space forms characterized by critical points of (1.3) have been investigated in [4,27]. For classification results of the critical points of (1.3), we refer to [7] and various unique continuation properties were studied in [8]. The stress-energy tensor of (1.3) has been systematically analyzed in [5].…”
Section: Introduction and Resultsmentioning
confidence: 99%
“…However, if r = 1, 2, 3 or in the case of a one-dimensional domain, both functionals (1.3) and (1.4) coincide. For an extensive analysis of (1.4) and a discussion of the differences between (1.3) and (1.4), we refer to the recent articles [3,6,8,27].…”
Section: Introduction and Resultsmentioning
confidence: 99%
“…In [11] it was shown that both 4-harmonic as well as ES − 4-harmonic maps satisfy the unique continuation property. The general structure of r-harmonic and ES-r-harmonic hypersurfaces in space forms has been investigated in [23].…”
Section: Introduction and Resultsmentioning
confidence: 99%